OBTAINING BIOTECHNOLOGICAL PRODUCTS ON THE BASIS OF ENZYMATIC CONVERSION OF PLANT WASTE AND PROSPECTS FOR THEIR USE (Academia Science Repository, 2023)
Enzyme preparations play a significant role in biotechnological processes for obtaining food products. The classification of enzymes, the specificity of their action on various substrates, and the processes for obtaining enzyme preparations based on microorganisms producing enzymes are presented. The monitoring of the world and domestic market of enzyme preparations used in the food industry was carried out. The issues of effective bioconversion of various types of plant raw materials to improve the quality of obtained juices, fruit drinks, reduce viscosity and increase the yield of biologically valuable components for the production of functional food products are considered; microbial raw materials - for obtaining protein-amino acid, vitamin food fortifiers, as well as food ingredients; animal raw materials - for the intensification of technological processes, processing of waste from the meat and dairy industries, as well as in cheese making to improve the quality of products. The proposed review is of scientific and practical interest for specialists in the field of biotechnology for the production of food products obtained on the basis of the enzymatic conversion of various types of agricultural raw materials.